A brain in flame; do inflammasomes and pyroptosis influence stroke pathology?. (March 2017) - Barrington, Jack; Lemarchand, Eloise; Allan, Stuart M.
Abstract: Stroke is one of the leading causes of death and disability worldwide. Inflammation plays a key role across the time course of stroke, from onset to the post‐injury reparative phase days to months later. Several regulatory molecules are implicated in inflammation, but the most established inflammatory mediator of acute brain injury is the cytokine interleukin‐1. Interleukin‐1 is regulated by large, macromolecular complexes called inflammasomes, which play a central role in cytokine release and cell death. In this review we highlight recent advances in inflammasome research and propose key roles for inflammasome components in the progression of stroke damage.